Effective Leadership, Work Environment and Work Culture as Main Factors of Job Satisfaction among Elementary School Teachers - Widyanarko, Rudy; Murniati, Ngurah Ayu Nyoman; Nugrahani, Dyah (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study addresses the problem of low teacher job satisfaction in public elementary schools in Boja District, Kendal Regency, which is believed to be influenced by ineffective leadership, unsupportive work environments, and fragmented school cultures. The objective of this research is to analyse the influence of effective school principal leadership, work environment, and work culture on teacher job satisfaction. Using a quantitative approach with an explanatory design, the study involved 199 teachers selected through a proportionate stratified random sampling method. Data were collected using a structured questionnaire and analysed through multiple linear regression. The findings revealed that both principal leadership (β = 0.128, p = 0.008) and work environment (β = 0.122, p = 0.009) significantly affect teacher job satisfaction. In contrast, work culture (β = 0.003, p = 0.094) does not show a statistically significant influence. The adjusted R² value of 0.594 indicates that the three variables explain 59.4% of the variation in job satisfaction. The study highlights the need to enhance leadership quality and work environments to improve teacher satisfaction and effectiveness. Although school culture shows potential, it must be translated into tangible practices and professional recognition to have a meaningful impact.